Magia entre las ruinas: estética de la destrucción, ruinenlust y actividad mágica en el mundo romano - Alfayé Villa, Silvia (2018)
his paper explores the significance and use of the ruins as loca magica in the Roman World, focusing on literary, epigraphical and archaeological sources. As liminal topographies invested of material, aesthetic and metaphorical meanings linked to destruction and death, and dwellings of supernatural powers, it will be demonstrated that ruins appeared as an ideal location for magical activities, mainly oriented to ruin victims' lives.
Keywords: Magia; Civilización clásica; Ruinas; Roma